Effectiveness of Internet-Based Cognitive Behavioral Therapy on Quality of Life Among Breast Cancer Survivors: Literature Review - Jayadi Idu, Cicirosnita; Nurcahyani, Rizka; Fadilah, Rizki; Sukma, Putri; Nur Fadhilah, Satrio; Asmieza Al Haq, Rifa (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Breast cancer is the most malignancy among women worldwide and is associated with long-term psychosocial burdens such as anxiety, depression, insomnia, and impaired quality of life. Given the rising number of survivors, effective and accessible psychological interventions are essential. Internet Cognitive Behavioral Therapy (ICBT) emerged as a promising digital solution. Objective to evaluate the effectiveness of ICBT in improving quality of life among breast cancer survivors. A systematic literature review was conducted using PubMed, ScienceDirect, and ResearchGate, focusing on studies published between 2020–2025. Article selection followed the PICOS framework, including randomized controlled trials (RCTs), quasi-experiments, pilot RCTs, and feasibility studies. Methodological quality was assessed using Joanna Briggs Institute (JBI) critical appraisal tools. The Results: From 249 identified studies, 10 met inclusion criteria. Evidence demonstrated that ICBT greatly diminished signs of depression, anxiety, insomnia, and distress, while improving cognitive function, coping ability, and overall quality of life for people who have recovered from breast cancer. The interventions were found to be flexible, accessible, and well-accepted. However, variations in effectiveness were observed depending on cancer stage, ongoing treatments, and psychosocial conditions. Conclusion: ICBT is an effective and innovative psychosocial intervention that enhances quality of life in breast cancer survivors. Its integration into healthcare systems is highly recommended, with tailored content to meet individual patient needs.